1992
DOI: 10.1136/hrt.67.5.351
|View full text |Cite
|
Sign up to set email alerts
|

Strenuous exercise, plasma fibrinogen, and factor VII activity.

Abstract: Objective-To assess the effect of physical activity on plasma fibrinogen and factor VII activity and thus on the risk of ischaemic heart disease.Design-Cross sectional survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 24 publications
0
38
1
4
Order By: Relevance
“…Fibrinogen concentration is elevated by a number of factors, including cigarette smoking, age, abdominal obesity and inactivity. 26,44 Although no relationship between fibrinogen and exercise was observed in the present study, a larger comparison of 3967 men aged 45-69 y found lower fibrinogen levels in those reporting strenuous exercise than in those reporting mild exercise after adjustment for differences in age, smoking and BMI. 44 In a study of 4057 middle-aged men, fibrinogen concentration was lower in normal-weight individuals who were fit than in normalweight individuals who were unfit.…”
Section: Exercise Waist Girth and Cvd Risk Factors G O'donovan Et Almentioning
confidence: 37%
See 1 more Smart Citation
“…Fibrinogen concentration is elevated by a number of factors, including cigarette smoking, age, abdominal obesity and inactivity. 26,44 Although no relationship between fibrinogen and exercise was observed in the present study, a larger comparison of 3967 men aged 45-69 y found lower fibrinogen levels in those reporting strenuous exercise than in those reporting mild exercise after adjustment for differences in age, smoking and BMI. 44 In a study of 4057 middle-aged men, fibrinogen concentration was lower in normal-weight individuals who were fit than in normalweight individuals who were unfit.…”
Section: Exercise Waist Girth and Cvd Risk Factors G O'donovan Et Almentioning
confidence: 37%
“…26,44 Although no relationship between fibrinogen and exercise was observed in the present study, a larger comparison of 3967 men aged 45-69 y found lower fibrinogen levels in those reporting strenuous exercise than in those reporting mild exercise after adjustment for differences in age, smoking and BMI. 44 In a study of 4057 middle-aged men, fibrinogen concentration was lower in normal-weight individuals who were fit than in normalweight individuals who were unfit. 45 In the present study, there was a trend for blood pressure to increase across subgroups, with significant differences in diastolic pressure apparent between lean exercisers and obese sedentary men.…”
Section: Exercise Waist Girth and Cvd Risk Factors G O'donovan Et Almentioning
confidence: 37%
“…Only few reports on the effects of physical exercise on FVII are available, and it seems that at least moderate exercise has no significant influence on FVII level [15][16][17] or the effect is at the most only relatively short-lived 18 . Dietary fat intake associates positively with FVIIc both in the fasting and postprandial states [19][20][21][22][23][24][25] .…”
Section: Coagulation Factor VIImentioning
confidence: 99%
“…Connely et al conducted a cross sectional survey of 3,967 male participants and found that strenuous exercise, which included jogging, cycling, and fast swimming lowered fibrinogen levels [26].…”
Section: Interventionmentioning
confidence: 99%
“…Exercise: Data in a few studies on exercise and fibrinogen levels have shown that mild to moderate exercise can lower fibrinogen levels [26][27][28][29].…”
Section: Interventionmentioning
confidence: 99%